The Use of Bamboo for Erosion Control and Slope Stabilization: Soil Bioengineering Works - Tardio, Guillermo (2018)
The potential of bamboo in erosion control and slope stabilization has been proven worldwide. Bamboos are being used as living plants as well as construction material in different soil bioengineering techniques in many countries. The soil and water bioengineering approach is combined with bamboo traits and mechanical properties. The existing accumulated experiences of using bamboo in soil and water bioengineering works, along with the existing standards and design guidelines, make bamboo species an essential and cost-effective material for erosion control and slope stabilization works. In this chapter, all the necessary aspects to be taken into account for an appropriate use of bamboo in soil bioengineering works are addressed, and the design approaches for soil bioengineering works using bamboos are presented.